Análisis del efecto de la degradación de biopelículas bacterianas del género Staphylococcus sp mediante la aplicación de nanopartículas de óxido de cobre sintetizadas química y biológicamente (2024)
The alarming increase in infections caused by multidrug-resistant microorganisms has become a global health crisis. This situation has raised widespread concern and has driven international efforts to understand, identify and combat Antimicrobial Resistance (AMR).